Formation of Mn hydrides from bis(trimethylsilylmethyl) Mn(II): A DFT study. (1st March 2020) - Hales, James J.; Trudeau, Michel L.; Antonelli, David M.; Kaltsoyannis, Nikolas
Graphical abstract: We recently reported the synthesis and characterization of KMH-1, a manganese hydride molecular sieve which projects sufficient performance to realise the DOE system targets for H2 storage and delivery. In this contribution, we explore computationally several series of reactions that could occur in the production of KMH-1 from bis(trimethylsilylmethyl) manganese (II). Abstract: We recently reported the synthesis and characterization of KMH-1 (Kubas Manganese Hydride – 1 [L. Morris et al., Energy Environ. Sci., 2019, 12, 1580–1591]), a manganese hydride molecular sieve which, if incorporated into a hydrogen storage system, projects sufficient performance to realise the DOE system targets for H2 storage and delivery. KMH-1 is amorphous and paramagnetic, making its characterization challenging, and how it is formed from its simple Mn(II) organometallic precursors is not fully understood. In this contribution, we explore computationally several series of reactions that could occur in the production of KMH 1 from bis(trimethylsilylmethyl) manganese (II) (Mn(TMSM)2 ), including the formation of hydrides, ways to generate the extended structure and reactions to produce species with Mn(I) centres (KMH-1 is believed to contain a substantial proportion of Mn(I)). We show that the most likely route to the formation of Mn hydrides is via elimination of tetramethylsilane (TMS) by reaction of Mn(TMSM)2 with H2 . These hydrides could then react to grow the extended KMH-1 structure via Mn hydride condensation reactions. Alternatively, multimetallic TMS-containing products could be formed via condensation reactions involving Mn(TMSM)2 and/or MnTMSM, after which the TMS ligand could be removed via elimination reactions with H2 . The formation of Mn(I) centres from Mn(II) hydrides is most likely via H2 elimination from Mn(II) hydrides.